Outcomes and process evaluation of a cluster-randomised participatory organisational intervention among German healthcare workers - Diego Montano; Marco Kuchenbaur; Richard Peter (BMC, 2023)
Abstract Background In the present investigation the results of the outcome and process evaluation of a participatory workplace intervention are reported. The intervention aimed to increase the workers' self-assessed physical and mental work ability. Methods The intervention was a two-arm, cluster-randomised trial with healthcare workers in 10 hospitals and one elderly care centre in Germany. Outcome data on workers were collected in questionnaires at baseline, and two follow-ups between 2019 and 2021. The intervention consisted of interviews and workshops, in which employees proposed measures for reducing the physical and psychosocial load and strengthening resources at work. Outcome data were analysed with linear-mixed regression models. The process evaluation was based on the thematic criteria proposed in previous literature and the collection of the type of intervention measures and their implementation status. Results The regression analysis did not provide evidence of treatment differences or reductions of psychosocial load in the intervention wards. The process evaluation suggested that the measures did not address specifically the self-assessed work ability. In addition, there was no indication that the intervention measures were causally related to the intended goals. Conclusions The planning and implementation of organisational interventions require a careful consideration of the definition of intervention goals, the theoretical rationale of the intervention and a project-oriented action plan during the delivery phase.